Marriage, Cohabitation, and Divorce in Later Life. Issue 2 (13th September 2017) - Brown, Susan L; Wright, Matthew R
Abstract: Older adults are at the forefront of family change as a declining share experiences lifelong marriage and rates of cohabitation and divorce in later life continue to rise. The goal of this article is to review recent scholarship on marriage, cohabitation, and divorce among older adults and identify directions for future research. The varied family experiences characterizing the later life course demonstrate the importance of moving beyond marital status to capture additional dimensions of the marital biography, including transitions, timing, duration, and sequencing. Cohabitation operates as an alternative to marriage for older adults and is increasingly replacing remarriage following divorce or widowhood. The gray divorce rate has doubled in recent decades as older adults abandon marriage in favor of unmarried partnerships or singlehood. The retreat from marriage among older adults raises important questions about the ramifications of family change for health and well-being as well as access to caregivers given that spouses historically have been the primary source of care.